2013
DOI: 10.1186/1741-7015-11-174
|View full text |Cite
|
Sign up to set email alerts
|

Safety of TNF-α inhibitors during IBD pregnancy: a systematic review

Abstract: BackgroundTumor necrosis factor (TNF)-α inhibitors are increasingly being used in inflammatory bowel disease (IBD). Because this chronic intestinal disorder often affects women of fertile age, it is essential to assess the effect of biologics on pregnancy outcome.MethodsWe performed a systematic review of the English-language literature to investigate if treatment with TNF-α blockers during pregnancy in women with IBD increases the risk of spontaneous abortions, preterm delivery, stillbirth, low birth weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 85 publications
(127 reference statements)
1
72
0
5
Order By: Relevance
“…Since that publication, several large population-based studies have been published that have examined this issue and medical management of the disease has continued to evolve. Data support the safety of thiopurines and biological medications in pregnancy [4,5], and patients have been counseled to delay conception based on disease activity to improve outcomes [6]. In addition, over the same time period, obstetricians have become increasingly more reluctant to deliver prior to 39 weeks secondary to a growing awareness of the adverse impact of late-preterm and early-term delivery [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since that publication, several large population-based studies have been published that have examined this issue and medical management of the disease has continued to evolve. Data support the safety of thiopurines and biological medications in pregnancy [4,5], and patients have been counseled to delay conception based on disease activity to improve outcomes [6]. In addition, over the same time period, obstetricians have become increasingly more reluctant to deliver prior to 39 weeks secondary to a growing awareness of the adverse impact of late-preterm and early-term delivery [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to one of the first studies, reporting a high rate of congenital malformations, including the VACTERL association (Vertebral defects, Anal atresia, Cardiac defects, Tracheoesophageal abnormalities, Renal and Radial anomalies and Limb defects) in foetuses exposed to TNFi, data subsequently collected from the experience in different diseases have not shown an increased risk of congenital abnormalities or a recurrent pattern of defects in a very large number of TNFi exposed pregnancies [2,[77][78][79][80][81][82][83]. Nevertheless, in 2015 Weber-Schoendorfer et al reported a significantly increased risk for major defects in 495 TNFi exposed pregnancies during the first trimester compared to 1542 controls (5% vs 1.5% -adjusted Odds Ratio 2.2, 95% CI 1.01, 4.8), without any correlation with VACTERL spectrum [84].…”
Section: Tnf Inhibitorsmentioning
confidence: 75%
“…The effect on the neonate is unclear and there are theoretical concerns about neonatal immunosuppression. However, data from the PIANO registry 26 are reassuring: third trimester anti-TNFα use had no effect on infant growth, development and immune development in the first year of life and a systematic review 27 found no increased risk of infections up to 1 year of age. There has been a single isolated case of fatal disseminated Bacillus Calmett-Guerin (BCG) in an infliximab-exposed infant who received the vaccine at 3 months of age.…”
Section: Biologicsmentioning
confidence: 99%